Review of cornea & contact lenses - Bailey, Gretchyn M. ([País no identificado] : Advanced Medical Optics, 2006)
La revista de cornea y lentes de contactos trata sobre las prácticas exitosas de lentes de contacto con pacientes orientados que sienten una experiencia gratificante y agradable.
INDICE - The hassles of hypoxia - Is it safe to go back into the water? - The young progressive GP-wearing Myope - Unique performance claims the story behind the label - Nerve toxin turned therapeutic botox helps with ophthalmic, neurologic and cosmetic applications - Reports of increased incidence of acanthamoeba keratitis a look at recent sudies on this rare infection - The science behind anti-infective therapy the fifth in a series about science and products, this roundtable discussion of manufacturer researchers examines anti-infective therapy. - Alternative uses of contact lenses in a pediatric population - Teens and contact lenses made for each other keys to success in the teen market - Pediatric GP fitting pictorial by Christine W. Sind
Review of cornea & contact lenses, se trabajó por analítica
El artículo está escrito en inglés
Incluye tabla
Incluye ilustración a colores
Incluye Preguntas de prueba
Incluye bibliografía en cada artículo
Keywords: OPTOMETRÍA -- PUBLICACIONES SERIADAS; ENFERMEDADES DE LOS OJOS -- PUBLICACIONES SERIADAS; OFTALMOLOGÍA -- PUBLICACIONES SERIADAS; SALUD VISUAL -- PUBLICACIONES SERIADAS